Aging and oral squamous cell carcinoma development: the role of cellular senescence - Niklander, Sven Eric; Aránguiz, Pablo; Faunes, Fernando; Martínez-Flores, René (Frontiers in Oral Health, 2023)
The gradual accumulation and inadequate renewal of senescent cells over time drive organismal aging. Senescent cells undergo altered gene expression and release inflammatory mediators collectively termed the senescence-associated secretory phenotype (SASP), which significantly contributes to a spectrum of age-related disorders, including cancer. In the context of carcinogenesis, the SASP produced by senescent cells has been implicated in the promotion of epithelial cancers, including oral squamous cell carcinoma (OSCC), the most common form of oral cancer. Senescent cells within the tumor microenvironment release factors that amplify the growth and invasiveness of neighboring cancer cells. Senotherapeutics, including senolytics and senomorphics, emerge as promising modalities to target senescent cells and their associated inflammatory factors, thereby opening novel avenues for augmenting the efficacy of cancer treatments. Here, we review the general aspects of cellular senescence, focusing on the relation between senescence-related inflammation with cancer development. We also analyze the available evidence linking cellular senescence with OSCC, highlighting possible clinical applications.